ГИМНАСТИКА ҲАРАКАТЛАРИНИ ЎРГАТИШДА ЎЙИН УСЛУБИНИНГ САМАРАДОРЛИГИ - Хайтметов, И.С. (SCIENCE and SOCIETY, 2022)
A set of exercises used physical education lessons at school has found its practical confirmation in the development of physical qualities of 10-11year old schoolchildren.